2008
DOI: 10.1136/gut.2007.135004
|View full text |Cite
|
Sign up to set email alerts
|

Association between chromosomal instability and prognosis in colorectal cancer: a meta-analysis

Abstract: CIN is associated with a worse prognosis in CRC, and should be evaluated as a prognostic marker, together with MSI status, in all clinical trials, particularly those involving adjuvant therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
240
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 312 publications
(258 citation statements)
references
References 112 publications
11
240
0
6
Order By: Relevance
“…Furthermore, although CIN to be a prognostic factor in patients with CRC, its precise role in tumor biology and its relation to MSI remains unclear. 11 To the best of our knowledge, and as derived from a recent metanalysis, 11 this study on MSI and DNA ploidy in patients with CRC is the second of only 2 publications that have examined these 2 features in combination, and the other study investigated only patients with colonic cancers who were recruited to adjuvant chemotherapy trials; those investigators demonstrated a prognostic significance for aneuploid cancers, but not for MSI. 17 Obviously, the roles of MSI and CIN will require further investigation to clarify their precise role in CRC development, prognosis, and prediction.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, although CIN to be a prognostic factor in patients with CRC, its precise role in tumor biology and its relation to MSI remains unclear. 11 To the best of our knowledge, and as derived from a recent metanalysis, 11 this study on MSI and DNA ploidy in patients with CRC is the second of only 2 publications that have examined these 2 features in combination, and the other study investigated only patients with colonic cancers who were recruited to adjuvant chemotherapy trials; those investigators demonstrated a prognostic significance for aneuploid cancers, but not for MSI. 17 Obviously, the roles of MSI and CIN will require further investigation to clarify their precise role in CRC development, prognosis, and prediction.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13] CIN is associated with aneuploid tumors; thus, ploidy serves as a surrogate marker for CIN in CRC. 11,12 Most previous studies on MSI status in patients with CRC have focused on survival and response to chemotherapy, for which recent data continue to produce equivocal results.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…CIN is more diffi cult to assess than MSI and hence is assayed less oft en. However, a meta-analysis of 3,094 patients with stage II or III CRC reported inferior overall survival associated with CIN (HR = 1.45, 95 % CI 1.27 -1.65) ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Oversikt over arbeider der man har studert den prognostiske verdien av DNA-ploidianalyse for pasienter med tykktarmskarsinom (2000 -16 I tillegg er det i tre store metaanalyser, som alle inkluderte over 5 000 pasienter (7,48,49), konkludert med at pasienter med aneuploide svulster har signifikant lavere femårsoverlevelse (hasardratio 1,45) enn pasienter med diploide svulster (48,49). Videre er det observert en mortalitetsreduksjon på >15 % for pasienter med diploide svulster (48) og sammenheng mellom aneuploiditet og mer avanserte kreftstadier (7).…”
Section: Tabellunclassified